GC – MS Analysis and Antiviral Efficacy of Lactiplantibacillus plantarum Postbiotic Extracts Against Infectious Haematopoietic Necrosis Virus - Mohammad Tamrin Mohamad Lal; Gilbert Ringgit; Zy Chee Wong; Leong Seng Lim; Fui Fui Ching; Ilham Misbakudin Al Zamzami; Abdul Aziz Jaziri; Muhamad Afiq Aziz; Hiroaki Saito; Motohiko Sano (Journal of Fish Diseases, 2026)
Infectious haematopoietic necrosis virus (IHNV) causes devastating economic losses in salmonid aquaculture and effective control measures are urgently needed. This study investigates the anti‐IHNV potential of postbiotics derived from Lactiplantibacillus plantarum . The crude postbiotic extract (PBP20o) and a neutralized version (PBP20a) were evaluated for cytotoxicity and antiviral activity in epithelioma papulosum cyprini (EPC) cells. Both extracts exhibited a safe concentration threshold of 1.15 μgmL −1 . Remarkably, treatment with PBP20o and PBP20a at this non‐cytotoxic concentration reduced IHNV titers by 0.82 log₁₀TCID₅₀/ml (84.9%) and 0.46 log₁₀TCID₅₀/ml (65.3%), respectively. The enhanced efficacy of the acidic extract might suggest a dual mechanism involving direct acid‐mediated viral inactivation combined with the action of pH‐stable bioactive metabolites. GC–MS identified three potential antiviral compounds, including such as trans‐cinnamic acid (RT = 33.688, A% = 0.39), pyrrolo[1,2‐a]pyrazine‐1,4‐dione, hexahydro‐3‐(2‐methylpropyl) (RT = 48.516, A% = 13.54) and hexadecanamide (RT = 56.226, A% = 3.11) from L. plantarum postbiotic. This study identifies L. plantarum postbiotics as a novel and promising source of antiviral compounds, offering a potential alternative strategy for mitigating IHNV outbreaks in aquaculture while ensuring biosafety for the target host and end consumers.

Black rice and its therapeutic potential: A Southeast Asian perspective on functional phytochemicals - Nur Sakinah George; Gilbert Ringgit; Shafiquzzaman Siddiquee; Noor Atiqah Aizan Abdul Kadir (Food and Humanity, 2026)

A Comprehensive Review of Endoparasite Infections in Marine Fish: Prevalence, Infection Factors, and Dominant Species - Gilbert Ringgit; Leong Seng Lim; Hon Jung Liew; Attabik Mukhammad Amrillah; Mohammad Tamrin Mohamad Lal (Current Microbiology, 2026)

GC-MS Profiling, Cytotoxicity and Antiviral Activity of Caulerpa lentillifera and C. macrodisca from Northern Coastal Waters of Borneo Island, Eastern Malaysia - Mohammad Tamrin Mohamad Lal; Elden Sai Long Chang; Zy Chee Wong; Leong Seng Lim; Muhammad Dawood Shah; Wahidatul Husna Zuldin; Gilbert Ringgit; Nur Azreen Arbi; Ahmad Hazim Abdul Aziz; Abdul Aziz Jaziri; Asep Awaludin Prihanto; Attabik Mukhamad Amrillah; et al. (Marine Biotechnology, 2026)

Impact of retrogradation on starch digestibility, predicted glycemic index, and nutritional composition in black and red rice - Nur Sakinah George; Yasmin Beng Houi Ooi; Yanty Noorzianna Abdul Manaf; Gilbert Ringgit; Shafiquzzaman Siddiquee; Noor Atiqah Aizan Abdul Kadir (Vegetos, 2026)
Pigmented rice, such as black and red rice, has garnered attention due to its unique bioactive profiles. Retrogradation is known to alter digestibility, glycemic response, and nutritional properties, yet its effects on pigmented rice remain less explored. This study aimed to evaluate the impact of starch retrogradation on the digestibility of starch, glycemic index, digestive enzyme inhibition, and nutritional characteristics of Sabah, Malaysia local black ( Tadong ) and red ( Merah ) rice varieties. Rice samples underwent retrogradation using a freeze-thaw-drying method: gelatinisation, cooling at 4 °C, drying at 60 °C, and then at 95 °C. Control samples were prepared without the cooling step. Starch fractions (rapidly digestible starch [RDS], slowly digestible starch [SDS], resistant starch [RS]), apparent amylose content (AAC), degree of retrogradation (DG), predicted glycemic index (PGI), enzyme inhibition (α-amylase, lipase), phenolic (TPC) and anthocyanin contents (TMAC), and overall nutritional composition were assessed using standardised analytical methods. Retrograded samples showed significantly lower RDS (20.93–25.47%) and higher RS (47.37–51.00%), AAC (24.83–26.43%), and DG (69.29–70.39%) than controls. The retrograded rice exhibited significantly reduced PGI and enhanced inhibition of pancreatic α-amylase (39.97–47.61%) and lipase (14.85–20.90%). Slight reductions in TPC and TMAC were observed, attributed to thermal processing. Retrogradation also significantly increased dietary fibre content and decreased moisture, both of which are beneficial for storage stability. The freeze-thaw-drying retrogradation method effectively improved starch digestibility, glycemic response, enzyme inhibitory activity, and dietary fibre content of pigmented rice, supporting its potential application in functional food formulations targeting metabolic and digestive health.

Etlingera Species of Borneo's wild gingers: traditional knowledge, phytochemistry, and modern applications - Gilbert Ringgit; Bo Eng Cheong; Muhammad Dawood Shah; Shafiquzzaman Siddiquee (Phytochemistry Reviews, 2026)

Syringic Acid in Canarium odontophyllum for Diabetes and Obesity – A Review - Gilbert Ringgit; Bo Eng Cheong; Muhammad Dawood Shah; Noor Atiqah Aizan Abdul Kadir; Shafiquzzaman Siddiquee (Cell Biochemistry and Biophysics, 2025)

Optimal formulation of bitter gourd and black galingale extract: Evaluation of effects on inflammation and oxidative stress-related genes - Christine Gustin; Gilbert Ringgit; Shafiquzzaman Siddiquee; Suryani Saallah; Khairul Azfar Bin Kamaruzaman (Food Bioscience, 2024)

Phenols, flavonoids and anthocyanins in Solanum lasiocarpum from Borneo: In vitro antioxidant activity and phytochemical profiling via LCMS Q-TOF - Gilbert Ringgit; Bo Eng Cheong; Muhammad Dawood Shah; Shafiquzzaman Siddiquee (Food Bioscience, 2024)